Jual Beli Online Dengan Barang Cacat Ditinjau Dari Hr. Ibnu Majah No. 2246 Dan Ahmad No. 17487 Serta Pasal 65 Ayat 2 UU No. 7 Tahun 2014 - Sabila, Kanisa; Arifin, Tajul (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study explores the Islamic legal perspectives on online trading of defective goods, considering hadiths, laws, and comparisons with positive law, in the context of the increasing electronic commerce in the modern world. Findings highlight the seller's obligation to transparency and responsibility for defective goods, as well as the rights of buyers, providing a basis for practical recommendations including enhancing information transparency, forming policy based on Sharia principles, educating business operators and consumers, developing dispute resolution mechanisms in accordance with Islamic law, and implementing technology to improve transparency and compliance. Thus, it is hoped that consumer protection in the context of online trading can be enhanced in line with the moral and ethical principles of Islam, which in turn will support the sustainable development of electronic commerce